Proses Pembuatan Video Hasil Pertanian Sebagai Media Sosialisasi Internal Instansi dan Masyarakat di Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian (BBP2TP): Pengabdian - Lilis Cucu Sumartini; Fujiyati; Sujana, Ujang; Putranto Widiatmoko, Roso (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This service presents the Agricultural Product Video Making Process as institutional and public internal socialization media in Indonesian Agricultural Technology Research and Development (BBP2TP) and applies qualitative method to provides the references and systematical or accurate occurrences from many sources using various data gathering techniques. Socializing media represents communication activities in delivering product surplus of either commodities or services and this media is quite substantial in order to persuade the commodities and services. BBP2TP has been socializing products research by media, such as flyer, leaflet, brochure, x-banner and video. Indonesian Agricultural Technology Research and Development (BBP2TP) is technical implementer unit (UPT) in study and development agricultural technology under the surveillance of Agricultural Research and Development Division Chairman and the socializing media certainly provides information and visualization of products’ study result. Obvious information can improve and effect people enthusiasm to use products’ study result. The expectation of using the designed and implemented is to be more effective and efficient than using conventional brochure, journal and institution website.